Motivasi Siswa Mengikuti Bimbingan Belajar di SMA Negeri 1 Kota Sungai Penuh - Putra, Fengki Andrita; Yusri, Yusri; Nurfahanah, Nurfahanah (Konselor, 2014)
Learning is process to give student that helpfrom learning difficulties, that maybe comes during learning process, so that student can get their optimal score. In study processing, the motivation is very important. The motivation is indispensable, because an individu didn’t have encouragement or desire in study,is imposible can do study activity well. It mean there was motivation in student self indirectly will grow up the spirit and passion in study. As a matter in fact, there are many student who have low learning motivation becausemany found that student always going out-going in from the class and doing something else during study process. This research is descriptif research and the purpose to describe about student’s motivation to follow learning process. The conclusion of the research is student’smotivation tofollow learning in good enough category. The implication of guidance and counseling service for student’s motivation to follow learning process through information service about increase the study motivation and individual counseling by way of knowing the matter in study that encountered in studying and giving problem solving.Learning is process to give student that helpfrom learning difficulties, that maybe comes during learning process, so that student can get their optimal score. In study processing, the motivation is very important. The motivation is indispensable, because an individu didn’t have encouragement or desire in study,is imposible can do study activity well. It mean there was motivation in student self indirectly will grow up the spirit and passion in study. As a matter in fact, there are many student who have low learning motivation becausemany found that student always going out-going in from the class and doing something else during study process. This research is descriptif research and the purpose to describe about student’s motivation to follow learning process. The conclusion of the research is student’smotivation tofollow learning in good enough category. The implication of guidance and counseling service for student’s motivation to follow learning process through information service about increase the study motivation and individual counseling by way of knowing the matter in study that encountered in studying and giving problem solving.